User Education Programs in Universit Libraries:Feedback from Faculty - Bandi, Ishappa; Ramakrishnegowda, K. C. (Journal of Information and Knowledge, 2016)
This article is based on analysis of data gathered from Social Science faculty in ten State Universities in Maharashtra that are conducting user education programs. 291 (82.97%) Social Science faculty responded to the questionnaire. Data analysis reveals that only 35.05% of the respondents attended user education programs. Most professors were 'Not aware' of the programs while more than half of 'Associate Professors' (54.29%) attended these programs. Majority (58.42%) of the Social Science faculty have 'not attended any program' - 'No time to attend' (43.20%), 'Lack of information' (36.80%) are the primary reasons for not attending these programmes. But majority of the faculty have indicated that these programs are useful to them (68.73%) and 97.50 percent of these respondents indicated that their 'accessing the Online Sources' will improve immensely.